Good Corporate Governance, Kepailitan dan Nilai Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia - Mahubessy, Victor Jonathan (E-Jurnal Akuntansi; Vol 31 No 1 (2021)DO - 10.24843/EJA.2021.v31.i01.p11, 2021)
This research was conducted with the aim of proving the effect of Good Corporate Governance, demonstrated by managerial ownership, institutional ownership, independent board of commissioners and audit committee as well as potential bankruptcy on Firm value. The population used by mining companies on the IDX in 2017 - 2019 was 15 companies observed after random sampling. The data analysis technique used is regression analysis. The results of this study provide evidence that the independent commissioner, potential bankruptcy, and audit committee have a significant effect on Firm value, while managerial ownership and institutional ownership have no significant effect on Firm value. Keywords : Company Value; Corporate Governance; Bankruptcy Potential.